Home » Past Questions » Mathematics » Simplify: (3\(\frac{1}{2} + 4\frac{1}{3}) \div (\frac{5}{6} - \frac{2}{3}\))

Simplify: (3\(\frac{1}{2} + 4\frac{1}{3}) \div (\frac{5}{6} - \frac{2}{3}\))


Question

Simplify: (3\(\frac{1}{2} + 4\frac{1}{3}) \div (\frac{5}{6} - \frac{2}{3}\))

Options

A) 1\(\frac{1}{4}\)

B) 8\(\frac{1}{2}\)

C) 35

D) 47

The correct answer is D.

Explanation:

(3\(\frac{1}{2} + 4\frac{1}{3}) \div (\frac{5}{6} - \frac{2}{3}\)) = (7\(\frac{3 + 2}{6}) \div \frac{(5 - 4)}{6}\)

7\(\frac{5}{6} \div \frac{1}{6} = \frac{47}{6} \times \frac{6}{1}\) = 47


More Past Questions:


Dicussion (1)

  • (3\(\frac{1}{2} + 4\frac{1}{3}) \div (\frac{5}{6} - \frac{2}{3}\)) = (7\(\frac{3 + 2}{6}) \div \frac{(5 - 4)}{6}\)

    7\(\frac{5}{6} \div \frac{1}{6} = \frac{47}{6} \times \frac{6}{1}\) = 47

    Reply
    Like